2021
DOI: 10.3390/gels7030127
|View full text |Cite
|
Sign up to set email alerts
|

Chondroitin Sulfate-Based Cryogels for Biomedical Applications

Abstract: Cryogels attained from natural materials offer exceptional properties in applications such as tissue engineering. Moreover, Halloysite Nanotubes (HNT) at 1:0.5 weight ratio were embedded into CS cryogels to render additional biomedical properties. The hemolysis index of CS cryogel and CS:HNT cryogels was calculated as 0.77 ± 0.41 and 0.81 ± 0.24 and defined as non-hemolytic materials. However, the blood coagulation indices of CS cryogel and CS:HNT cryogels were determined as 76 ± 2% and 68 ± 3%, suggesting a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 50 publications
0
10
0
Order By: Relevance
“…It is known in the literature that HNTs inhibit the AG enzyme [ 57 ]. Here, the AG enzyme inhibition ability of PDOPA@HNT was also studied, and we compared the neat HNTs with PDOPA@HNTs at the same concentration (2.0 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…It is known in the literature that HNTs inhibit the AG enzyme [ 57 ]. Here, the AG enzyme inhibition ability of PDOPA@HNT was also studied, and we compared the neat HNTs with PDOPA@HNTs at the same concentration (2.0 mg/mL).…”
Section: Resultsmentioning
confidence: 99%
“…Some polymers provide an iron-chelating ability and can be used to inhibit iron toxication in the body [ 38 ]. The Fe(II)-chelating capacities of CS microgels and CS − [R] + microgels were examined in a DI water solution in the 125–2000 µg/mL concentration range in accordance with the literature [ 37 ]. In our previous work, the Fe(II) chelation ability of CS was not observed, even at a 2000 μg/mL concentration.…”
Section: Resultsmentioning
confidence: 99%
“…In accordance with the literature, CS microgel and CS − [R] + microgel aqueous solutions were prepared at 2000 µg/mL concentrations and were diluted to 1000, 500, 250, and 125 µg/mL. Then, 140 µL of CS microgel or CS − [R] + microgel suspension solution was added into 96 wells [ 37 ]. Then, 20 µL of 1 mM Fe (II) aqueous solution was added to them, and measurements were obtained using a microplate reader (Thermo Multiskan Go, USA) at 562 nm.…”
Section: Methodsmentioning
confidence: 99%
“…When comparing hydrogels and cryogels, hydrogels are crosslinked 3D networks with a high water content [ 9 , 10 ]. Hydrogels are known to swell better than cryogels, however; Hixon et al synthesized silk fibrin cryogels and hydrogels and showed that cryogels can swell to a greater extent [ 11 , 12 , 13 ]. Cryogels, on the other hand, have such important properties as flexibility, large pores, high mechanical strength, short diffusion paths and good biocompatibility [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cryogels can also have shape-memory properties and can be synthesized in various forms, such as powder, columns, beads, membranes, monoliths, and injectable forms [ 16 , 17 , 18 , 19 , 20 , 21 ]. The high porosity makes them suitable for use as macroporous cell-laden scaffolds for tissue constructions [ 13 ]. These cryogels can be used in a variety of biomedical applications, including diagnostics, therapeutics, drug delivery and tissue engineering.…”
Section: Introductionmentioning
confidence: 99%